Curcumin and neuroplasticity: epigenetic mechanisms underlying cognitive enhancement in aging and neurodegenerative disorders - Jiao, Hao; Wang, Xiuying; Zhang, Dahui; Zhou, Shengxue; Gao, Feng (Frontiers in Aging Neuroscience, 2025)
Aging and neurodegenerative diseases are characterized by cognitive decline, impaired neuroplasticity, and epigenetic dysregulation. Curcumin, a bioactive polyphenol derived from Curcuma longa, has gained significant attention for its neuroprotective properties, particularly in enhancing cognitive function through epigenetic mechanisms. This review explores the multifaceted role of curcumin in modulating key molecular pathways involved in neuroplasticity, including histone modifications, DNA methylation, and non-coding RNA regulation. Additionally, curcumin influences neurogenesis, synaptic remodeling, and mitochondrial biogenesis, which are critical for maintaining brain function in aging and neurodegenerative conditions such as Alzheimer’s and Parkinson’s disease. By targeting neuroinflammatory and oxidative stress pathways, curcumin further supports cognitive resilience and neuronal survival. We also discuss the therapeutic implications of curcumin as a potential epigenetic modulator and neurogenic agent, emphasizing its synergistic effects with lifestyle interventions such as physical activity and dietary strategies. Despite promising preclinical and clinical findings, challenges related to curcumin’s bioavailability and translational efficacy remain. Future research should focus on optimizing delivery systems and exploring combination therapies to enhance curcumin’s neuroprotective benefits. This review highlights curcumin as a promising candidate for promoting cognitive longevity and mitigating neurodegeneration through epigenetic reprogramming.